Pengembangan Lembar Kerja Siswa (LKS) Berorientasi Pada Proyek Penguatan Profil Pelajar Pancasila Kelas V SDN Ngadisari 1 tahun Ajaran 2022-2023 - Ferdina, Vifian Lestin; Wardana, Ludfi Arya; Kasdriyanto, Didit Yulian (CV. ITTC INDONESIA, 2024)
This research is conducted due to the low ability of students to understand the material in the Pancasila Student Profile Strengthening (P5) project learning and the lack of innovative teaching tools used by educators, which leads to students' lack of enthusiasm during classroom learning. The purpose of this developmental research is to produce teaching materials for the Pancasila Student Profile Strengthening (P5) project subject aimed at creating comprehensive and meaningful learning experiences for students, with a focus on strengthening the understanding of the values of Pancasila Sustainable Lifestyle. This research method utilizes the Research and Development model according to Borg and Gall. The research procedure includes preliminary research and data collection, product planning, development of initial product format, initial field testing, product revision, main field testing, revision of operational field testing products, and refinement of the final product as the ultimate outcome. The research subjects include two content experts and one media expert for validation testing. Data collection techniques employ questionnaires or surveys. The data type is qualitative descriptive. The final score from the assessment by the content expert is a form of evaluation conducted by content expert I on the aspect of the objectives of the developed LKS product, yielding an average score of 5. This data, when interpreted, indicates that in terms of the objectives of the product developed by the researcher, it falls within the criteria of